Legitimasi Pencatatan Pernikahan dalam Negara Hukum: Telaah Epistemologi Bayani Muhammad Abid Al-Jabiri - Anisa, Anisa; Faizah, Eka Zahrotul (Studi Multidisipliner: Jurnal Kajian Keislaman, 2025)
This study aims to analyze the epistemology of bayani as an approach in understanding religious texts and examine its implications for the urgency of marriage registration in the legal context in Indonesia. This study uses a qualitative method with a content analysis approach. The main source of data for this research is the work of Muhammad Abid al-Jabiri, namely Bunyah al-'Aql al-'Arabi, which is used as a conceptual basis to understand the framework of bayani epistemology. Secondary data sources include scientific journals, books, and laws and regulations relevant to the issue of marriage registration in Indonesia. The analysis is carried out by tracing the structure of bayani thinking that places the text (nash) as the main source of knowledge and makes the authority of the text as the basis for legitimacy in the formation of law. The results of the study show that bayani epistemology emphasizes the importance of understanding religious texts through the principle of correspondence between the meaning of the text and social reality. In the context of marriage, marriage registration is a concrete form of textual authorization efforts to suit modern social and legal needs. Thus, marriage registration is not only administrative, but has epistemological and moral dimensions as a form of responsibility for social clarity and benefits. Therefore, marriage registration is seen as very urgent in order to prevent mistakes, legal uncertainties, and potential disputes in the future.